Phasor measurement unit integration: A review on optimal PMU placement methods in power system - Noureen, Subrina Sultana; Roy, Vishwajit; Bayne, Stephen B. (2017 IEEE Region 10 Humanitarian Technology Conference (R10-HTC), 2017)
The Phasor Measurement Unit (PMU) is an imperative part for monitoring, protecting and controlling the current power system. For the current power systems, PMUs not only offer the synchronized measurements of real-time data of voltage but also the current and frequency. Placement of PMUs in each bus for monitoring the system is not feasible from economic point of view and also for big data handling. So it is an obligatory matter to reduce the number of PMUs in the bus system with the aim of attaining the maximum power system observation. Different techniques are being applied from past to present to solve this optimum PMU placement (OPP) problem such as heuristic method, mathematical programing. Heuristic method is a quick experience-based technique for solving the optimization problems. Various optimization methods for solving the OPP problems are being reviewed in this paper.